Rejecting the Rainbow Serpent: An Aboriginal Artist's Choice of the Christian God as Creator - Anderson, Sallie (The Australian journal of anthropology, 2001)
In this paper, I illustrate the way one Aboriginal artist challenged what he perceived as an essentialised concept of Aboriginality, by rejecting rainbow serpent iconography. The motivations for this rejection were the artist's strong belief in the Christian God as creator and his reaction against New Age representations of Aboriginality in which the rainbow serpent signifies Aboriginal spirituality and is posited as the single creator for all of Aboriginal Australia. A conflict arose at the artist's gallery when he refused to exhibit a rainbow serpent painting by another Aboriginal artist. Publicised in the local newspaper, the rejection of these artworks started a brief public debate about the role of Christianity in Aboriginal culture. The various positions adopted by the Aboriginal protagonists highlight the complex processes of negotiation, dialogue and debate surrounding diverse constructions of identity.